Facilitating the development of stencil applications using the Heterogeneous Programming Library. (18th April 2017) - Viñas, Moisés; Fraguela, Basilio B.; Andrade, Diego; Doallo, Ramón
Summary: Stencil computations are very common in scientific codes. Heterogeneous systems achieve good results solving these problems, but their programming is complex because of the ghost regions required in multi‐device implementations and the difficulty to properly exploit their hardware. The Heterogeneous Programming Library (HPL) is a recent framework that improves the programmability of heterogeneous devices. This paper describes two extensions of HPL focused on stencil computations. The first one allows to automatically update the ghost regions they involve. The second one automates the implementation of the computational kernels of these algorithms. In our evaluation, the first mechanism reduces on average the number of lines of code and the Halstead programming effort of the host code of comparable HPL baselines by 34% and 64.2%, respectively, while the second contribution reduces these metrics by 72% and 79% in the computational kernels, respectively. Also, the first technique has negligible performance overheads, while the second one matches the performance of manually developed kernels. As an added benefit, the facilitation of the development of these codes thanks to these techniques helps programmers experiment with optimizations suited for this applications such as the ghost cell expansion technique, which provides speedups of up to 13% in our experiments.